2012
DOI: 10.1039/c2an16279b
|View full text |Cite
|
Sign up to set email alerts
|

The electrochemical performance of graphene modified electrodes: An analytical perspective

Abstract: We explore the use of graphene modified electrodes towards the electroanalytical sensing of various analytes, namely dopamine hydrochloride, uric acid, acetaminophen and p-benzoquinone via cyclic voltammetry. In line with literature methodologies and to investigate the full-implications of employing graphene in this electrochemical context, we modify electrode substrates that exhibit either fast or slow electron transfer kinetics (edge- or basal- plane pyrolytic graphite electrodes respectively) with well char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 59 publications
1
68
1
Order By: Relevance
“…6a depicts the linear relationship between the oxidation peak currents and DA concentration in the range of 0.59-43.955 μM. The corresponding linear regression equation is defined as I pa = 37.4099+0.5996C DA (R=0.992), and the lower detection limit for DA is observed to be 0.59 μM (S/N=3), which is lower than previously reported results [27][28][29]. Meanwhile, a similar experiment was conducted with UA in the presence of 8 μM DA.…”
Section: Uamentioning
confidence: 39%
See 1 more Smart Citation
“…6a depicts the linear relationship between the oxidation peak currents and DA concentration in the range of 0.59-43.955 μM. The corresponding linear regression equation is defined as I pa = 37.4099+0.5996C DA (R=0.992), and the lower detection limit for DA is observed to be 0.59 μM (S/N=3), which is lower than previously reported results [27][28][29]. Meanwhile, a similar experiment was conducted with UA in the presence of 8 μM DA.…”
Section: Uamentioning
confidence: 39%
“…As shown in the inset of Fig. 6b, the linear relationship between the oxidation peak currents of UA and the UA concentration is defined as I pa =24.262+0.1001C UA (R=0.997) in the range of 12.6-413.62 μM and the lower detection limit is observed to be 12.6 μM (S/N=3), which is lower than what was previously reported [28,29]. The above results show that GE/Au/GE/CFE is well response for the determination of DA and UA.…”
Section: Uamentioning
confidence: 39%
“…Due to rather poor electrocatalytic activity of intrinsic graphene and graphite [25][26][27], the electrodes were activated by anodization [28,29]. It has been shown that during electrochemical oxidation, several functional groups connect to the graphite basal plane and many multivacancies and small etch pits appear [30].…”
Section: Introductionmentioning
confidence: 99%
“…This feature is in good agreement with the specification data of graphene nanopowder and graphene nanoplatelet aggregates given by Graphene Supermarket and Strem Chemicals, respectively. Based on the literature, the low O/C ratio refers to the near true nature of graphene [53]. The main difference between GO and rGO is that GO is with higher oxygen content than rGO [54,55].…”
Section: Surface Characterisation Of Graphene-family Nanomaterialsmentioning
confidence: 99%